Doom to Disaster? Industrial Pollution in Sidoarjo 1975—2006 - Ronal Ridho'i (Lembaran Sejarah, 2017)
Massive industrialization causes various pollutions (water, air, land and noise). Until early 2000s, facts proved that the environmental condition of Sidoarjo getting worse because of the high level of pollution in this area. This paper aims to explain industrial pollution, regulation of pollution and the debate of pollution cases in Sidoarjo since 1975-2006. Author uses an environmental history approach to analize this phenomenon, and peruses archival sources, newspapers, magazines and interview. This research finds out that industrial pollutions in Sidoarjo still continuously happen until today. Meanwhile, the govenrment regulations were not effectively decrease industrial pollutions because of collusion practice between industrialists and local government, and even with the military personnel particularly during the New Order. This paper proves that the government regulations and law enforcement about the environment were not resolving the pollution problems in Sidoarjo.